Giant Magnetoresistance-based Biosensor for Detection of Influenza A Virus - Krishna, Venkatramana D.; Wu, Kai; Perez, Andres M.; Wang, Jian-Ping (Frontiers in Microbiology, 2016)
We have developed a simple and sensitive method for the detection of influenza A virus (IAV) based on giant magnetoresistance (GMR) biosensor. This assay employs monoclonal antibodies to viral nucleoprotein (NP) in combination with magnetic nanoparticles (MNPs). Presence of influenza virus allows the binding of MNPs to the GMR sensor and the binding is proportional to the concentration of virus. Binding of MNPs onto the GMR sensor causes change in the resistance of sensor, which is measured in a real time electrical readout. GMR biosensor detected as low as 1.5 × 102 TCID50/mL virus and the signal intensity increased with increasing concentration of virus up to 1.0 × 105 TCID50/mL. This study showed that the GMR biosensor assay is relevant for diagnostic application since the virus concentration in nasal samples of influenza virus infected swine was reported to be in the range of 103 to 105 TCID50/mL.